Identification and Validation of an Apoptosis-Related Gene Prognostic Signature for Oral Squamous Cell Carcinoma - Wang, Shuqin; Zhang, Sien; Lin, Zhi; Ma, Jingxin; Zhu, Lijun; Liao, Guiqing (Frontiers in Oncology, 2022)
To identify an apoptosis-related gene (ARGs) signature for predicting prognosis in patients with oral squamous cell carcinoma (OSCC), we analyzed the data of a training set from TCGA. Then, we obtained a six risk gene signature related to apoptosis for predicting OSCC survival through univariate Cox regression, LASSO, and multiple Cox regression analysis. Kaplan–Meier analysis and ROC analysis showed a good prognostic ability of the model both in the internal training set and external validation set. Univariate Cox regression and multivariate Cox regression indicatedthat the model was an effective independent prognostic factor of OSCC. Furthermore, we established a nomogram using these ARGS to predict the 3- and 5-year survival probability of OSCC patients. Moreover, we evaluated the immune cell infiltration in each tumor sample and found obvious, different patterns between the low-risk and high-risk groups. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed the biological characteristics and signaling pathways associated with this signature in OSCC. The expression of these risk genes in clinical specimens were higher in the poor survival group than the well survival group by immunohistochemical staining analysis. In conclusion, we identified an apoptosis-related gene signature associated with prognosis of OSCC. These genes could also be targets for the treatment of OSCC.